2021
DOI: 10.2807/1560-7917.es.2021.26.41.2002041
|View full text |Cite
|
Sign up to set email alerts
|

Heatwave-associated Vibrio infections in Germany, 2018 and 2019

Abstract: Background Vibrio spp. are aquatic bacteria that prefer warm seawater with moderate salinity. In humans, they can cause gastroenteritis, wound infections, and ear infections. During the summers of 2018 and 2019, unprecedented high sea surface temperatures were recorded in the German Baltic Sea. Aim We aimed to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
7
31
0
Order By: Relevance
“…The majority of vibriosis cases in the study countries were domestic and males were more frequently affected than females, consistent with other reports [12, 21]. Even though the majority of cases were present among adults, about a fifth of the detected cases were among children up to 14 years of age, who mostly had ear infections and mild vibriosis; severe infections on the other hand were found to be associated with increasing age.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The majority of vibriosis cases in the study countries were domestic and males were more frequently affected than females, consistent with other reports [12, 21]. Even though the majority of cases were present among adults, about a fifth of the detected cases were among children up to 14 years of age, who mostly had ear infections and mild vibriosis; severe infections on the other hand were found to be associated with increasing age.…”
Section: Discussionsupporting
confidence: 90%
“…It is well documented that vibriosis is more frequently reported in summer [2, 6, 11, 12, 18]. Our results from 2018 confirm this pattern with the majority of infections occurring in summer months.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study provides a detailed overview on the occurrence of vibriosis in the Nordic and Baltic Sea regions in 2018. In a context of epidemiological and microbiological findings as well as studies conducted from 2014 to 2018 [ 11 , 12 ], our results highlight the importance of vibriosis as a concern to public health in this geographical area. Even though the data had been collected using different systems, the study countries reported similar patterns of sex and age group distribution in the affected population.…”
Section: Discussionsupporting
confidence: 65%